Homeric γόον 'bewailed' (Ζ 500). - Nussbaum, Alan J. (Scripta Classica Israelica, 2025)
The 3rd pl. indicative γόον at Iliad Z 500 has always presented problems. It means 'bewailed' and belongs to present γοάω but might be imperfect and might be aorist. Neither is straightforward in form. Imperfect, the analysis of most of the ancients because it is 'κάλλιον,' is shown here in addition to conform to a particular pattern of Homeric narration, while aorist, following the minority ancient view, requires either an indefensible, effectively pre-Greek, ancestral form or a morphological analogy that is unworkable. The form taken by this consequently demonstrable imperfect has most often been explained via an elaborate phonological scenario that is questionable, it is argued, in both of its key points. It has also, less usually, been morphologically accounted for as a slightly disguised version of the expected 3rd pl. imperfect of the "Aeolic" inflection of Ionic etc. γοάω. This is the correct view, it is maintained here, but can be made a much stronger hypothesis by a demonstration that there are two (but not three) additional pieces of evidence for the "Aeolic" inflection of this very verb in epic language--one of which, pres. infinitive γοήμεναι, is standardly recognized as "Aeolic," but never evaluated and deployed in the discussion of γόον; while the other, the irregularly short iterative imperfect form γόασκε in the Hymn to Aphrodite, has never been utilized as evidence bearing on the problem of γόον at all.